HISTORY AND ORIGIN OF PUBLIC ECONOMICS - Vasudevan, C. (International Journal of Research -GRANTHAALAYAH, 2020)
History and origin of Public Economics Presented as the evolutionary nature of its disciplinary interest to for student curriculaum and a method of analysis for Govt. Policy doiers. The subject matter of this article has fully involved to discuss from its history and origin from classical periods to its in modern times. Further this article explained the nature and characteristics of public economics in collaboration, as a method of analysis of many dominant issues like externalities, market failure and distortions effects is to be as subject of studies in its growth.